Minor Remnants from Solna Street: Isaac Celnikier’s Post-war Sketches and the Holocaust Experience - Zuzanna Benesz-Goldfinger (Miejsce)
When Isaac Celnikier (1923-2011) decided to emigrate to France, reacting to the escalation of anti-Semitic sentiments in Poland in 1957, he left behind artwork he had created in the 1940s and 50s. Among these was a collection of illustrations for Yiddish short-stories, written by Abraham Reisen in the first three decades of the 20th century and published in one volume by the “Yiddish Bukh” publishing house in 1957. Although in a letter to Aleksander Lewin, his educator at the Janusz Korczak’s Orphanage, Celnikier called this collection “minor remnants from Solna street which are of little importance,” these are artworks that he created during the post-war period, a quintessential testimony that he left behind. He survived the Bialystok ghetto, the Stutthof, Auschwitz III (the so-called Buna) and Flossenbürg Nazi camps. Around April 20, 1945, he was found by American soldiers under a pile of corpses. In the artist and survivor’s post-war reading, the stories of Reisen were construed as a prefiguration of the Holocaust. In the sketches analyzed, Celnikier projected his own personal experience of the Shoah: the breakup of family ties, disconnection from the continuity of Jewish tradition, and the border experience of surviving under a pile of corpses.